2010
DOI: 10.1007/s12034-010-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

PEDOT-PSSA as an alternative support for Pt electrodes in PEFCs

Abstract: Poly (3,4-ethylenedioxythiophene) (PEDOT) and poly (styrene sulphonic acid) (PSSA) supported platinum (Pt) electrodes for application in polymer electrolyte fuel cells (PEFCs) are reported. PEDOT-PSSA support helps Pt particles to be uniformly distributed on to the electrodes, and facilitates mixed electronic and ionic (H + -ion) conduction within the catalyst, ameliorating Pt utilization. The inherent proton conductivity of PEDOT-PSSA composite also helps reducing Nafion content in PEFC electrodes. During pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…In the spectra, peaks at 1034 cm −1 , 1394 cm −1 , and 1489 cm −1 are due to C-O-C bond stretching of ethylenedioxy group and a set of peaks at 420 cm −1 , 620 cm −1 and 820 cm −1 are assigned to the C-S bond of thiophene ring (Han et al 2007). Peaks appearing at 1200 cm −1 and 930 cm −1 due to the SO − 3 and S-OH stretching of PSS are observed in both the spectra (Tintula et al 2010). MWNTs/PEDOT-PSS nanocomposite shows features similar to the standard PEDOT-PSS polymeric composite.…”
Section: Structural Characterization Of Nanocompositementioning
confidence: 86%
“…In the spectra, peaks at 1034 cm −1 , 1394 cm −1 , and 1489 cm −1 are due to C-O-C bond stretching of ethylenedioxy group and a set of peaks at 420 cm −1 , 620 cm −1 and 820 cm −1 are assigned to the C-S bond of thiophene ring (Han et al 2007). Peaks appearing at 1200 cm −1 and 930 cm −1 due to the SO − 3 and S-OH stretching of PSS are observed in both the spectra (Tintula et al 2010). MWNTs/PEDOT-PSS nanocomposite shows features similar to the standard PEDOT-PSS polymeric composite.…”
Section: Structural Characterization Of Nanocompositementioning
confidence: 86%
“…To overcome this problem, conducting polymers and their composites were reported in the literature as a catalyst support for fuel cells owing to their high electronic and proton conductivity as well as chemical stability and high oxidation resistance . A number of conducting polymers, such as polypyrrole (PPy), polyaniline (PANI), and poly(3,4‐ethylenedioxythiophene) (PEDOT) were investigated as conducting catalyst support materials for different fuel cell types . Zhao et al .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the electrocatalytic activity of galvanostatically prepared PANI was much higher than that of potentiostatically prepared PANI for methanol oxidation. Tintula et al . reported the utilization of PEDOT/PSSA (PSSA=poly(strenesulfonic acid))‐supported Pt electrodes for polymer electrolyte fuel cells (PEFCs) and they showed that PEDOT/PSSA demonstrates better fuel‐cell performance with a power density of 605 mW cm −2 compared to Pt/Vulcan XC‐72R (575 mW cm −2 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations